Adaptive algorithm for fields storage in calculations of dynamics of continuous media with history or time delayed feedback - Zakharov, Andrey Pavlovich; Bratsun, Dmitriy Anatolievich (Computational Continuum Mechanics, 2013)
A new method for calculating the dynamics of spatially-extended system the current state of which depends on the whole or partial previous evolution of the system is proposed. The method is based on an adaptive algorithm for optimal data storage by storing in the memory not all previous states of the system, but only some selected of them, called the basic states. The intermediate states are restored by interpolation between the basic states. The use of this technique allows the numerical calculations to be implemented on computer systems without large RAM memory. The effectiveness of the developed algorithm is demonstrated by the example of a numerical simulation of the reaction-diffusion of proteins responsible for biorhythms in cells.